Europäische Dimensionen des ,,Don Quijote in Literatur, Film, Kunst und Musik" - Altenberg, Tilmann; Meyer-Minnemann, Klaus (Hamburg University Press, 2007)
Like no other novel, the "Don Quixote" by Miguel de Cervantes has fascinated readers time and again for four centuries. Written in Spain in the early 17th century, which at that time played a major role in shaping the destiny of Europe, the novel soon became the epitome of Spanish literature and culture. From Madrid he started affecting the rest of Europe and inspired thinkers, poets, artists, composers and later also filmmakers. The volume's eight contributions explore central aspects of the Cervantine novel and explore its reception and processing in literature, art, film and music in the European context.